Love in action: writings on nonviolent social change - Nhất Hạnh, Thích (Parallax Press, 2021)
"A collection of key writings on nonviolent social change for activists from the 1960s until 2013 by Vietnamese peace advocate and Zen monk Thich Nhat Hanh, including the script of a play set during the war in Vietnam"--